High-density polyethylene superfine fiber tarpaulin as well as preparation method and application thereof
Through the hydrospinning consolidation process of HDPE microfiber materials, the problems of poor flexibility and low production efficiency of traditional tarpaulins are solved, and high-strength, lightweight, and portable high-density polyethylene microfiber tarpaulins are prepared, with excellent Waterproof, breathable and radiation cooling performance, suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411446582.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Traditional tarpaulins have high density, thickness, poor flexibility and low fit, which limit their application in areas such as personal protection and high-value special-shaped target coverage. The existing microfiber materials have low production efficiency and poor mechanical properties, making it difficult to meet high strength, light and thinness. Commercial demand for tarpaulin.
High-density polyethylene (HDPE) microfiber material is used to form a dense nonwoven structure through hydrotonic consolidation process, adjust the energy and mass of the water needle per unit area, and prepare a porosity of 82.7%-85.9% and a modal pore diameter of 6-8 μm high density polyethylene microfiber tarpaulin.
It achieves high strength, light weight, softness, portability and excellent waterproof, breathable and radiation cooling performance. The longitudinal and transverse tensile fracture strengths are 217.8 N and 168.0 N respectively, with a hydrostatic pressure resistance of >4500 Pa, and a reflectivity of 94.3%. , suitable for outdoor sports, material storage and military supplies.
Smart Images

Figure CN119221204A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of textile materials and relates to the preparation of high-performance fibers, in particular to a high-density polyethylene ultrafine fiber tarpaulin and a preparation method and application thereof. Background Art
[0002] As a physical barrier between materials and the external environment, tarpaulin has the characteristics of beauty, external force protection, and moisture and heat regulation. It can not only be used for outdoor personal protection, but also for collective protection such as material storage, sports facility preservation, and military equipment covering and camouflage. It is an important part of safety protection equipment. Traditional tarpaulins are mostly coated modified fiber materials and multi-layer structure composite materials with high mechanical strength and excellent waterproof properties. However, traditional tarpaulins are often dense and thick. In the specific application process, they often show problems such as poor flexibility, low fit and inconvenience, which greatly limits their application in personal protection and high-value special-shaped target coverage. Therefore, the development of high-strength and light fiber materials has become a common research hotspot in the fields of sports, safety protection and functional textiles.
[0003] Flexible fiber materials prepared by non-woven processes such as electrospinning, meltblowing and bicomponent spunbond-spunlace have a unique dense structure of ultrafine fiber non-woven materials, showing good shielding properties, and have attracted widespread attention in the industry. However, they have the industry problems of low production efficiency and poor mechanical properties, which are difficult to meet the commercial application needs of high-strength and light tarpaulins. The current non-woven web technology of ultrafine fiber materials has the advantages of a wide source of raw materials (high-density polyethylene and polypropylene, etc.) and high production efficiency, and can be used for large-scale production of ultrafine fiber webs. High-density polyethylene (HDPE), as a common polymer raw material for preparing ultrafine fiber webs, has excellent thermal stability and formability, and is widely used in the field of non-woven products. Unfortunately, although the existing non-woven products prepared with HDPE ultrafine fiber webs have high strength and excellent shielding properties, they also show poor hand feel and a strong "plastic feel". The spunlace non-woven web consolidation process is a flexible web consolidation technology that uses high-speed water jets to promote fiber movement and interweave and entangle with each other, which can serve the consolidation of HDPE ultrafine fiber webs. In order to study the hydroentanglement consolidation method of HDPE ultrafine fiber web and the performance of HDPE hydroentangled ultrafine fiber material, this application conducted an in-depth exploration. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a high-density polyethylene (HDPE) ultrafine fiber tarpaulin and a preparation method and application thereof.
[0005] The technical solution of the present invention is achieved in this way: A method for preparing a HDPE ultrafine fiber tarpaulin, comprising the following steps: The web-forming method of HDPE ultrafine fiber material is as follows: HDPE slices are heated, softened and melted into a polymer melt, and then sent together with the solvent into a mixing kettle at a temperature of 205 ° C and a pressure of 20 MPa to form a spinning solution with a mass fraction of 15%-25%. The solvent is composed of dichloromethane (mass ratio of 50%-80%) and methanol (mass ratio of 20%-50%), which are configured according to a certain mass ratio. The spinning solution is sprayed into the atmospheric pressure environment through a decompression chamber. During this process, the solvent evaporates instantly to form HDPE ultrafine fibers. The HDPE ultrafine fibers are divided, turned and deposited on the receiving mesh curtain under the action of the steering plate to form an HDPE ultrafine fiber web.
[0006] Hydroentanglement of HDPE ultrafine fiber material: The HDPE ultrafine fiber web was hydroentangled using a hydroentanglement system (SC-600, Changzhou Xinrenli Textile Equipment Co., Ltd.). The HDPE ultrafine fiber web passed through multiple hydroentanglement heads and formed into HDPE ultrafine fiber material under the impact of water jets.
[0007] The parameters of the above-mentioned water stab consolidation are: main stab pressure 6-10 MPa, feeding speed 3m / min, water needle energy 1699.3-8299.7 kJ / m 2 .
[0008] Furthermore, the water injection energy is 2105.9-8299.7 kJ / m 2 .
[0009] The high-density polyethylene ultrafine fiber tarpaulin prepared by the above method.
[0010] The porosity of the high-density polyethylene microfiber tarpaulin is 82.7%-85.9%, the modal pore size is 6-8 μm, and the surface density is 90-110 g / m 2 .
[0011] The high-density polyethylene microfiber tarpaulin has a water contact angle of 140±5°, a hydrostatic pressure resistance of >4500 Pa, a softness score of >80, a reflectivity of 94.3%, and an outdoor radiation cooling capacity that is 11.2°C higher than that of pure cotton cloth.
[0012] The above-mentioned high-density polyethylene ultrafine fiber tarpaulin is used in the preparation of outdoor sports, material storage and military materials.
[0013] The present invention has the following beneficial effects: 1. This application uses high-density polyethylene (HDPE) as raw material, and prepares a HDPE ultrafine fiber material after a hydroentanglement consolidation process on the HDPE ultrafine fiber net; based on the characteristics of the prepared HDPE ultrafine fiber net with a diameter distribution of 1~6 μm, a uniform, dense and stable ultrafine fiber non-woven structure can be formed under the impact of a water jet. By adjusting the water jet energy and unit area mass, the porosity can be adjusted and controlled within 82.7%~85.9% and the modal pore size can be adjusted and controlled within 6~8 μm, thereby achieving improved mechanical properties; 110g / m 2 The sample was at 2821.9 kJ / m 2 Under the impact of water jet, the longitudinal and transverse tensile breaking strengths of the sample are 217.8 N and 168.0 N respectively. Thanks to the low surface energy of HDPE fiber and the nonwoven structure formed by the HDPE ultrafine fiber spunlace solid network, the sample has a high hydrostatic pressure resistance of 6695.7Pa and good air permeability and water vapor permeability.
[0014] 2. The HDPE microfiber material samples of this application show high softness, easy folding and portability, and excellent special-shaped fit. The softness score is higher than 80, the reflectivity is 94.3%, and the outdoor radiation cooling capacity is 11.2 °C higher than that of pure cotton cloth. It can not only be used for high-strength and lightweight tarpaulins, but also provide cases for the development of functional products such as sports equipment, outdoor protection and military equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 This is the principle diagram of the nonwoven process of HDPE ultrafine fiber material.
[0017] Figure 2 Electron microscope images of the surface and cross-section of samples with different water needle energies.
[0018] Figure 3 are the characteristic parameters of the sample structure; (a) fiber diameter distribution of 55 g / m² sample, (b) pore size distribution of samples with different water injection energies, and (c) pore size distribution of samples with different unit area masses.
[0019] Figure 4 Force-displacement curve during sample stretching, where (a) is the longitudinal stretching curve of the sample, and (b) is the transverse stretching curve of the sample.
[0020] Figure 5 This is the morphology of droplets on the surface of HDPE microfiber material.
[0021] Figure 6 This is a diagram of the waterproof and breathable performance of the sample.
[0022] Figure 7 The radiation cooling performance of the sample; (a) light transmittance curve, (b) light emissivity curve, and (c) test temperature curve.
[0023] Figure 8 is the softness score of the sample; where (a) is the softness score of samples with different water injection energies, and (b) is the softness score of samples with different mass per unit area.
[0024] Fig. 9 The samples are shown in the following figure for portability, special-shaped lamination and printing effects; (a) easy folding and portability, (b) special-shaped lamination, and (c) easy ink absorption. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, the experimental methods used in the following experimental examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0027] HDPE chips, grade: 5000S, density 0.95 g / m 3 , melting point 140~160 ℃, Beijing Yanshan Petrochemical Co., Ltd.
[0028] Example: Preparation of HDPE ultrafine fiber material 1. Web forming of HDPE ultrafine fiber material Figure 1 The nonwoven process preparation principle of HDPE ultrafine fiber material is shown. The preparation process is as follows: HDPE slices are heated, softened and melted into a polymer melt, and then sent together with the solvent into a mixing kettle at a temperature of 205 ℃ and a pressure of 20 MPa to prepare a spinning solution with a mass fraction of 18%. The solvent is prepared by dichloromethane and methanol in a mass ratio of 80:20. The spinning solution is sprayed into the atmospheric pressure environment through a decompression chamber, and the solvent evaporates instantly to form HDPE ultrafine fibers. The HDPE ultrafine fibers are divided, turned and deposited on the receiving mesh curtain under the action of the steering plate to form an HDPE ultrafine fiber web.
[0029] 2. Hydroentanglement of HDPE ultrafine fiber materials The HDPE ultrafine fiber web was hydroentangled using a hydroentanglement system (SC-600, Changzhou Xinrenli Textile Equipment Co., Ltd.). The HDPE ultrafine fiber web passed through multiple hydroentanglement heads and formed an HDPE ultrafine fiber material under the impact of water jets.
[0030] Table 1 shows the main spunlace process parameters.
[0031] A total of samples No. 1-10 were prepared using the above process, and samples No. 1-10 were tested and characterized below.
[0032] 3. Testing and Characterization 3.1 Morphology and structure The surface and cross-sectional micromorphology of the sample were observed using a scanning electron microscope (JSM-IT200, JEOL, Japan) at an accelerating voltage of 5 kV. The sample was gold-sprayed before observation. 50 fibers were randomly selected from the surface electron micrographs to measure their diameters and obtain the fiber diameter distribution of the sample.
[0033] Thickness: The thickness of the samples was tested using a thickness meter (32CHQF 1030, Deqing Shengtaixin Electronic Technology Co., Ltd.) according to the test standard "GB / T 24218.2-2009 Textiles - Test methods for nonwoven fabrics - Part 2: Determination of thickness". The thickness of each group of samples was tested 5 times; the average value was taken as the sample thickness.
[0034] Mass per unit area: The mass per unit area (100cm) was measured using an electronic balance (BT456A 300, Shenzhen Botu Electronic Technology Co., Ltd.) according to the test standard "GB / T 24218.1-2009 Textile nonwoven fabric test methods Part 1: Determination of mass per unit area" 2 ) The quality of the samples; each group of samples was tested 5 times and the average value was taken.
[0035] Porosity: The porosity of the sample was calculated using formula (1). (1) Where: n is the porosity, %; p is the density of HDPE fiber, g / m 3 ; m is the mass per unit area, g / m 2 ; δ is the thickness, m.
[0037] The pore size distribution of the sample was tested using a pore size tester (PSM 165, Topas, Germany) according to the test standard "ISO 4003-1997 Determination of pore size in bubble test of permeable sintered metal materials". The test sample was a circle with a diameter of 2 cm, and the test liquid was Topar (Topas, Germany, surface tension: 16.0 mN / m).
[0038] like Figure 2-Figure 3 As shown, Figure 2 Electron microscope images showing the surface and cross-section of samples with different water needle energies. Figure 3 The sample structure characteristic parameters are shown. Figure 2 It can be seen from (a) to (e) that the HDPE ultrafine fiber material prepared based on the hydroentanglement consolidation process exhibits typical ultrafine fiber nonwoven structural characteristics. The circular ultrafine fibers with a diameter of 1 to 6 μm are randomly distributed in the horizontal direction, forming a dense ultrafine fiber network. The HDPE ultrafine fiber material prepared based on the hydroentanglement consolidation process exhibits more hydroentangled nonwoven structural characteristics, that is, the ultrafine fibers are entangled with each other and show a certain "bundling" phenomenon, and this phenomenon will become more obvious with the increase of water needle energy. Combined with Table 1, it can be seen that an increase in water needle energy will lead to a decrease in thickness and porosity. For 55 g / m 2 For samples, when the water injection energy is 1699.33 kJ / m 2 When the water needle energy increases to 8299.7 kJ / m 2 When the thickness is reduced to 0.277 mm, the porosity and modal pore size are reduced to 82.4% and 6.9 μm, respectively. This is because the impact of high-energy water jets will enhance the larger displacement transfer of fibers, thereby forming a denser entanglement between fibers, and the volume and size of the pores between fibers are also reduced. In addition, the modal pore size of HDPE ultrafine fiber material samples is inversely proportional to the mass per unit area ( Figure 3 (c)). As the sample mass per unit area increases from 90 g / m 2 Increased 110 g / m 2 , the proportion of pores between 6 and 8 μm increased from 43.1% to 78.3%. This is because the number of fibers stacked in the thickness direction of the sample increases with the increase of the mass per unit area.
[0039] 3.2 Mechanical properties Tensile fracture: The tensile fracture strength of the samples was tested using an electronic fabric strength tester (HD026S-100, Nantong Hongda Experimental Instrument Co., Ltd.) according to the test standard "GB / T 24218.3-2010 Textile nonwoven fabric test methods Part 3: Determination of breaking strength and elongation at break (strip method)". The samples were cut into 20 cm × 5 cm, and the tensile speed was 150 mm / min.
[0040] Bursting strength: The bursting strength of the samples was tested using a bursting strength tester (YG026MD-250, Wenzhou Fangyuan Instrument Co., Ltd.) according to the test standard "GB / T 19976-2005 Determination of bursting strength of textiles - Steel ball method". The samples were cut into a circle with a diameter of 10 cm, and the bursting speed was 100 mm / min.
[0041] The force-displacement curve of the HDPE ultrafine fiber material sample during tensile fracture is as follows Figure 4 As shown in (a) to (b), the performance index parameters are shown in Table 2. By comparing the force-displacement curves, it can be seen that all curves show similar change patterns. In the early stage of stretching, the force value shows a nonlinear increase. This shows that the microstructure of the HDPE ultrafine fiber material prepared based on the hydroentanglement consolidation technology is relatively loose, and it is easy to deform and elongate under the action of external force. As the stretching proceeds, the fibers of the HDPE ultrafine fiber material are rearranged along the force direction and present a tension state, accompanied by the breakage and slippage of certain fibers. In the later stage of stretching, as the number of fiber breakage and slippage increases, tensile fractures are formed, and the force value decreases rapidly from the highest value. It should be noted that the speed at which the force value of the sample decreases from the highest value during the transverse stretching process is significantly lower than that during the longitudinal stretching process, that is, more slippage between fibers is shown.
[0042] Table 2 Mechanical properties of samples Combination Figure 4 It can also be seen from Table 2 that as the water injection energy increases from 1699.3 kJ / m 2 Increased to 8299.7 kJ / m 2 , the longitudinal and transverse tensile breaking strength increased from 103.8 N and 68.9 N to 134.3 N and 84.6 N, respectively. At the same time, the longitudinal and transverse tensile breaking elongation increased from 27.2% and 18.3% to 32.7% and 23.3%, respectively. This is because as the water needle energy increases, the fibers become more entangled and the friction between the fibers increases. Similarly, the bursting strength of the sample also increased from 112.0 N to 138.7 N. In addition, under the condition that the water needle energy remains unchanged, the longitudinal and transverse tensile breaking strengths both increase with the increase in the unit area mass. Specifically, when the unit area mass of the sample increases from 90g / m2 Increased to 110 g / m 2 When the longitudinal and transverse tensile fracture strengths are increased to 217.8 N and 168.0 N, respectively. Finally, by comparing the longitudinal and transverse tensile fracture data of the samples, it can be found that the longitudinal tensile fracture strength of all samples is significantly greater than the transverse tensile fracture strength. This is because during the fiber web forming process of the HDPE ultrafine fiber material, the HDPE fibers are deposited on the receiving mesh curtain and are subjected to the directional force of the receiving mesh curtain, which results in a certain directional arrangement in the longitudinal direction; this is also the main reason why the transverse tensile fracture tensile curve of the HDPE ultrafine fiber material sample shows a longer slippage length.
[0043] An interesting discovery: 55g / m 2 The tensile strength of HDPE microfiber material samples is much higher than 45g / m 2 Polypropylene meltblown nonwoven material (about 10.2 times in the longitudinal direction and 11.3 times in the transverse direction) and 20 g / m 2 Polypropylene spunbond nonwoven material (about 3.1 times in the longitudinal direction and 4.5 times in the transverse direction), roughly equivalent to 70g / m 2 Viscose and polyester spunlace nonwoven materials.
[0044] 3.3 Waterproof and breathable performance Contact angle: The static water contact angle and rolling water contact angle of the sample were measured using a contact angle meter (SDC-350, Dongguan Shengding Company) according to the test standard "GB∕T 42694-2023 Detection and evaluation of anti-wetting performance of textile surfaces - contact angle and rolling angle". The measuring liquid was 5 μL of deionized water.
[0045] Hydrostatic pressure resistance: The hydrostatic pressure resistance of samples was tested using a fully automatic hydrostatic pressure tester (YG826G, Ningbo Textile Instrument Factory, China) according to the test standard GB / T 4744 Testing and evaluation of the waterproof performance of textiles. The liquid seepage rate was 10 mm / s; each group of samples was tested 5 times and the average value was taken.
[0046] Air permeability: The air permeability of the samples was tested using a fully automatic air permeability meter (YG416E-Ⅲ, Ningbo Textile Instrument Factory, China) according to the test standard "GB / T 24218.15-2018 Textile nonwoven fabric test methods Part 15: Determination of air permeability". The test pressure difference was 100 Pa and the test area was 20 cm 2 ; Each group of samples was tested 5 times and the average value was taken.
[0047] Water vapor transmission rate: The water vapor transmission rate of the samples was tested using a cup method water vapor transmission rate tester (W3, Jinan Languang Electromechanical Technology Co., Ltd., China) according to the standard "GB / T 12704.2-2009 Textile fabric water vapor permeability test method Part 2: Evaporation method". The test conditions were: ambient temperature was 40 ℃; each group of samples was tested 5 times and the average value was taken.
[0048] Excellent waterproof ability and good permeability are the key indicators for HDPE microfiber materials to be used in the tarpaulin field, which are usually characterized by hydrostatic pressure resistance, air permeability and water vapor permeability.
[0049] Figure 5 The figure shows the morphology of droplets on the surface of HDPE ultrafine fiber material. It can be seen from the figure that, benefiting from the low surface energy HDPE macromolecular structure and the smooth, ultrafine HDPE fiber morphology, the HDPE ultrafine fiber material sample has excellent resistance to common liquids such as water, milk, tea and cola. The water contact angle of the HDPE ultrafine fiber material sample prepared in this paper is 140±5°. The results of the hydrostatic pressure resistance test show that the hydrostatic pressure resistance of the prepared samples is greater than 4500 Pa, and increases with the increase of the water needle energy. Specifically, when the water needle energy is 1699.3 kJ / m 2 、2105.9kJ / m 2 、2821.9kJ / m 2 4703.2 kJ / m 2 、8299.7kJ / m 2 , and the hydrostatic pressure resistance is 4557 Pa, 4688 Pa, 4779 Pa, 4804 Pa, and 4905 Pa respectively. This is mainly because the water needle energy improves the density of the HDPE ultrafine fiber material structure. At the same time, as the sample unit area mass increases from 90 g / m 2 Increased to 110 g / m 2 , the hydrostatic pressure resistance of the sample increased to 6695.7 Pa, an increase of about 9.8%.
[0050] The air permeability and water vapor permeability test results show that the air permeability and water vapor permeability of HDPE microfiber material samples both show a decreasing trend with the increase of water injection energy. Specifically, when the water injection energy is 1699.3 kJ / m 2 、2105.9kJ / m 2 、2821.9kJ / m 2 4703.2 kJ / m 2 、8299.7 kJ / m 2When the air permeability is 60.6 mm / s, 56.9 mm / s, 52.8 mm / s, 49.3 mm / s, 45.1 mm / s, the water vapor transmission rate is 2165.6 g / (m 2 ·24h)、2017.9 g / (m 2 ·24h)、1968.3 g / (m 2 ·24h)、1913.0 g / (m 2 ·24h)、1805.1 g / (m 2 ·24h). This is because when the water jet energy increases, the water jet drives the fibers in the material to move and make them more densely arranged, the transmission channels for water vapor in the material will be reduced, and the water vapor permeability will decrease. In addition, the increase in the unit area mass of the sample will also create a stronger barrier to the passage of water vapor and reduce the water vapor permeability. The increase in the unit area mass of the HDPE ultrafine fiber material sample shows a decreasing trend in the air permeability and water vapor permeability of the sample. Specifically, when the unit area mass is 90g / m 2 , 95g / m 2 , 100g / m 2 , 105g / m 2 , 110g / m 2 At this time, the air permeability was 48.3 mm / s, 40.8 mm / s, 39.2 mm / s, 36.2 mm / s, and 30.8 mm / s, and the water vapor permeability was 2321.2 g / (m 2 ·24h)、2145.9 g / (m 2 ·24h)、1819.8g / (m 2 ·24h)、1706.4 g / (m 2 ·24h)、1676.6 g / (m 2 ·24h). In addition, Figure 6 The air permeability application experiment (test water depth is 5 cm) using HDPE microfiber material samples as waterproof layer shows that the lower air can pass through the HDPE microfiber material smoothly and form fine and uniform bubbles in the upper water. This experiment shows that HDPE microfiber material samples have good application capabilities in the fields of waterproofing, outdoor sports, etc.
[0051] 3.4 Radiative cooling performance Reflectivity: The reflectivity of the samples was tested using a UV-visible spectrophotometer (Color i5, X-rite, USA).
[0052] Emissivity: A Fourier transform infrared spectrometer is used to test the absorptivity of a material in the mid-infrared band (8-14 μm). According to Planck’s law, the thermal absorption capacity of an object is equal to its thermal emission capacity, and the emissivity of the material is obtained.
[0053] Radiative cooling capacity: The radiative cooling capacity of the sample was tested using a self-made radiative cooling test device, which consisted of a foam box wrapped in aluminum foil and a multi-channel temperature tester. A 100 cm 2 During the test, the sample is covered on the surface of the foam box and a layer of PE film is covered on the sample. A multi-channel temperature tester is used to monitor the temperature changes in the box.
[0054] Figure 7 (a) to (b) show the transmittance curve and emissivity curve of HDPE ultrafine fiber material samples. It can be seen that the samples prepared under different water spunlace pressures have high transmittance in the atmospheric transparent window, that is, they can better dissipate heat to the external environment. Comparing the two curves, it can be seen that 2105.9 kJ / m 2 The transmittance of the sample prepared by water injection energy is 42.6%, which is higher than 1699.3 kJ / m 2 The transmittance of the sample prepared by water injection energy is 34.8%. Figure 7 (b) It can be seen that the sample has a high reflectivity in the 350~760nm band. As the water needle energy increases from 1699.3kJ / m 2 Increased to 8299.7 kJ / m 2 When the water injection energy is 8299.7 kJ / m 2 The reflectivity can reach up to 94.3%. The above results show that the prepared HDPE ultrafine fiber material can effectively reflect sunlight. Figure 7 (c) It can be seen that the internal cavity temperature covered by HDPE microfiber material is significantly lower than that of the pure cotton fabric in the control test, which is reduced by 11.2℃, and has significant radiation cooling ability. In addition, the reduction of water needle energy also has a certain enhancement effect on the cooling effect. 3.5 Softness The softness score of the samples was tested using a PhabrOmeter 3 (NUCYBERTE-K, USA) according to the test standard GB / T 8942-2016 Determination of paper softness. Each group of samples was tested 3 times and the average value was taken.
[0055] Figure 8 , Fig. 9The softness score of HDPE ultrafine fiber material and its easy portability, special-shaped lamination and printing effect are shown respectively. It can be seen that thanks to the morphology of the prepared HDPE ultrafine fiber net and the flexible entanglement effect of the hydroentanglement method, the HDPE ultrafine fiber material exhibits high softness, easy folding and portability and excellent special-shaped lamination. Figure 8 It can be found from (a) to (b) that the softness scores of HDPE microfiber material samples are all higher than 80, and can be controlled by adjusting the water injection energy and unit area mass. Fig. 9 (a) It can be seen that the excellent softness improves the portability of HDPE microfiber materials during application. The HDPE microfiber material with a spreading area of 15×17 cm is about 20 times smaller than the fully spread area after folding. It can not only be rolled into a 3 cm ball, but also folded into a 3×5 cm rectangular handkerchief, which can meet the requirements of easy folding and portability in different scenarios, and can be used for the target ( Fig. 9 (b)) provides all-round coverage and plays a role in safety protection. In addition, HDPE microfiber materials are also very suitable for printing, signing pens, crayons and other printing and writing, which can present a clear effect, providing the possibility of improving the functionality of tarpaulins in terms of aesthetic decoration, camouflage protection and safety marking.
[0056] Implementation effect analysis This application aims to solve the problem that the HDPE ultrafine fiber mesh has poor hand feel and strong "plastic feel", which makes it difficult to meet the commercial application requirements of high-strength and light tarpaulins. A HDPE ultrafine fiber material is developed using the hydroentanglement consolidation process. The following conclusions are drawn by studying the sample morphology, structure and performance: 1) Based on the prepared HDPE ultrafine fiber web with a diameter distribution of 1~6 μm, a uniform, dense and stable ultrafine fiber nonwoven structure can be formed under the impact of a water jet.
[0057] 2) By adjusting the water needle energy and unit area mass, the porosity can be adjusted and controlled within 82.7%~85.9% and the modal pore size can be adjusted within 6~8 μm, thereby improving the mechanical properties; 110 g / m 2 The sample was at 2821.9 kJ / m 2 Under the impact of water jet, the longitudinal and transverse tensile breaking strengths of the sample are 217.8 N and 168.0 N, respectively.
[0058] 3) Thanks to the low surface energy of HDPE fibers and the ultrafine fiber nonwoven structure formed by the hydroentanglement consolidation process, the sample has a high hydrostatic pressure resistance of 6695.7 Pa and good air permeability and water vapor permeability.
[0059] 4) HDPE microfiber material samples showed high softness, easy folding and portability, and excellent conformability to special shapes. The softness scores were all above 80, the reflectivity was 94.3%, and the outdoor radiation cooling capacity was 11.2 ℃ higher than that of pure cotton cloth. It can not only be used for high-strength and lightweight tarpaulins, but also provide cases for the development of functional products such as sports equipment, outdoor protection and military equipment.
[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-density polyethylene ultrafine fiber tarpaulin, characterized in that: Here are the steps: (1) High-density polyethylene is melted and mixed with a solvent to prepare a spinning solution, which is then sprayed under reduced pressure to form high-density polyethylene ultrafine fibers; (2) The high-density polyethylene ultrafine fibers in step (1) are separated and deposited on a receiving mesh curtain to form a polyethylene ultrafine fiber web; (3) The polyethylene microfiber web of step (2) is hydroentangled to obtain a high-density polyethylene microfiber tarpaulin.
2. The method for preparing the high-density polyethylene ultrafine fiber tarpaulin according to claim 1, characterized in that: In the step (1), the solvent is a mixture of dichloromethane and methanol in a mass ratio of 4:1; the mass fraction of the spinning solution is 10%-30%.
3. The method for preparing the high-density polyethylene ultrafine fiber tarpaulin according to claim 2, characterized in that: The mixing temperature is 180-260° C. and the pressure is 10-50 MPa.
4. The method for preparing the high-density polyethylene ultrafine fiber tarpaulin according to claim 2, characterized in that: The process parameters of the water-jet spunlace in step (3) are set as follows: main spunlace pressure 6-10 MPa, feed speed 1-5 m / min, water spunlace energy 1699.3-8299.7 kJ / m 2 .
5. The method for preparing the high-density polyethylene ultrafine fiber tarpaulin according to claim 2, characterized in that: The water injection energy is 2105.9-8299.7 kJ / m 2 .
6. High-density polyethylene ultrafine fiber tarpaulin prepared by the method described in any one of claims 1 to 5.
7. The high-density polyethylene ultrafine fiber tarpaulin according to claim 6, characterized in that: The high-density polyethylene microfiber tarpaulin has a porosity of 82.7%-85.9%, a modal pore size of 6-8 μm, and a surface density of 90-110 g / m 2 .
8. The high-density polyethylene ultrafine fiber tarpaulin according to claim 7, characterized in that: The high-density polyethylene microfiber tarpaulin has a water contact angle of 140±5°, a hydrostatic pressure resistance of >4500 Pa, a softness score of >80, a reflectivity of 94.3%, and an outdoor radiation cooling capacity that is 11.2°C higher than that of pure cotton cloth.
9. Use of the high-density polyethylene ultrafine fiber tarpaulin according to any one of claims 6 to 8 in the preparation of outdoor sports and material storage.
10. Use of the high-density polyethylene ultrafine fiber tarpaulin according to any one of claims 6 to 8 in the preparation of military supplies.
Citation Information
Patent Citations
Novel antibacterial breathable fabric and preparation method thereof
CN115074917A
High-strength flash spinning textile and manufacturing method thereof
CN115491783A
Dry wipe
CN1509356A
House building top layer tarpaulin
CN200949287Y
Nonwoven fabric composed of three-dimensional reticulated fiber
JP1989132856A
